The role of schizotypal traits and the OXTR gene in theory of mind in schizophrenia: A family-based study. Issue 1 (2020) - Giralt-López, M.; Miret, S.; Soler, J.; Campanera, S.; Parellada, M.; Fañanás, L.; Fatjó-Vilas, M.
Abstract: Background: There is consistent evidence that theory of mind (ToM) is impaired in schizophrenia (SZ); however, it remains unclear whether such deficits are trait- or state-dependent. We evaluated ToM in patients with schizophrenia spectrum disorders (SSDs), their healthy first-degree relatives, and controls to test its suitability as an endophenotypic marker. We also studied the modifying effect of markers of clinical and genetic liability to SZ (schizotypy and genetic variability in the oxytocin receptor gene: OXTR ) on ToM in healthy individuals. Methods: The sample included 38 stable SSD patients, 80 unaffected first-degree relatives, and 81 controls. ToM was assessed using the Hinting Task (HT) and schizotypy via the Schizotypal Personality Questionnaire-Brief (SPQ-B), which generates interpersonal (SPQ-IP), cognitive-perceptual (SPQ-CP), and disorganization (SPQ-D) scores. The polymorphism rs53576 of OXTR was genotyped. Results: Patients presented poorer HT performance than relatives and controls ( p  = 0.003 and p  < 0.001). High SPQ-IP and SPQ-CP scores correlated with poorer ToM performance in relatives ( p  = 0.010 and p  = 0.030), but not in controls. OXTR was not associated with HT scores, but it showed a modifying effect within controls; high SPQ-CP was related to HT poorer performance conditional to GG genotype ( p  = 0.007). Conclusions: ToM deficits were present in patients but not in unaffected relatives or controls. However, our data indicate the usefulness of clinical and genetic liability markers to characterize differences in ToM abilities within healthy individuals. Then, the observed link between ToM and SZ liability suggests the putative role of ToM as an endophenotypic marker. Nevertheless, new analyses in larger samples are needed.